Concussion in Sports - McCrea, Heather J. (SAGE Publications, 2013)
CONTEXT: Recently, concussion has become a topic of much discussion within sports. The goal of this review is to provide an overview of the literature concerning the definition of concussion, management of initial injury, return to play, and future health risks. EVIDENCE ACQUISITION: This article reviews the most recent findings on recognizing and managing sports-related concussion, which has become a significant health risk. We reviewed articles from the literature discussing concussion and its effects. RESULTS: Though concussion patients typically have negative head imaging, imaging is warranted in those with severe mechanism, significant loss of consciousness, focal neurologic deficit, or worsening symptoms. The existence of “second-impact syndrome,” whereby a first minor head injury predisposes an athlete to later catastrophic injury, remains controversial; however, it is clear that concussion has significant effects on a patient and should be considered carefully in return-to-play decisions. CONCLUSIONS: A comprehensive understanding of concussion and its related risks is important in making return-to-play decisions as well as health care and league policy.